Normalized Matched Filter for Blind Interference Suppression in Filter Bank Multicarrier Spread Spectrum Systems - Taylor Sibbett; Hussein Moradi; Behrouz Boroujeny (IEEE Access, 2022)
This paper proposes and analyzes a modification to the standard matched filtering operation utilized in filter-bank multicarrier spread spectrum (FB-MC-SS) communications. This modification suppresses the impact of partial-band interferers without a priori knowledge of their location within the band of transmission and/or their power characteristics. A performance analysis of the proposed matched filter, which indicates its usefulness in environments where interference is likely to be experienced, is presented. It is shown that whereas the standard matched filter proves to be ineffective for packet detection and timing acquisition in such harsh environments, the modified matched filter successfully removes the harmful effects of interferers. This is found to be a unique feature of FB-MC-SS which is non-existent in other alternative spread spectrum methods.